'Our Second Capital on the Banks of the Thames': The Evolution of the Anglophilia of Czechoslovak Exiles in Britain during the Second World War. (3rd July 2022) - Kłusek, Johana
ABSTRACT: The study is the first to examine Anglo-Czechoslovak relations during the second world war from the perspective of discourse analysis. It reconstructs the evolution of the Czechoslovak exiles' Anglophilia through articles published in three major exile newspapers – Čechoslovák, Mladé/Nové Československo and Nová svoboda – between October 1939 and May 1945. It claims that the new significant Other, whose image included numerous idealizations as well as objective reflections, liberated exiled Czechs and served as an important guide in the quest for a better future for their own country. The study also demonstrates how quickly favourable conditions can create fruitful transcultural space between nations that had, hitherto, been separated by geography, culture and language.